PENGARUH KUALITAS PUPUK UREA BERSUBSIDI TERHADAP KEPUASAN KONSUMEN PT. PUPUK SRIWIDJAJA PADA UD. UTAMA KUTOARJO (STIE Rajawali Purworejo, 2021)
This study aims to determine the effect of the quality of subsidized urea fertilizer on consumer satisfaction of PT. Pupuk Sriwidjaja at UD. Main Kutoarjo. This study uses data collection techniques and surveys with questionnaires as well as literature study. The sample used with simple random sampling technique, amounting to 60 people. The related variable in this study is the quality of subsidized urea fertilizer on consumer satisfaction of PT. Pupuk Sriwidjaja Palembang at UD. Utama Kutoarjo with a simple correlation analysis method. The data analysis technique used in this study used a Likert scale to measure respondents' opinions and test instruments to test the instruments that were compiled. The test instruments used are validity test, reliability test, correlation coefficient, simple linear regression, coefficient of determination, and partial test (t test). Simple linear regression test results.Based on a simple linear regression test, it can be seen that the fertilizer quality variable increases by one unit, it will be followed by an increase in the farmer satisfaction variable, namely 0.226 which has a significant value in a positive direction, so it can be said that the direction of the influence of the X variable on Y is positive. The result of the coefficient of determination shows the R2 value of 0.124, which means that the contribution of the variable consumer satisfaction is 12.4% while the rest is influenced by other variables not examined, such as fertilizer allocation and prices. The results of the t-test obtained that the t-count value is greater than t-table (2.865 > 2.0017), then the null hypothesis which states that there is no positive and significant effect between fertilizer quality on farmer satisfaction is rejected and the working hypothesis (Ha) which states that there is a positive and significant influence between the quality of fertilizer on farmer satisfaction is accepted.